P6_2 The Pink Mist-ery - Kelly, Aidan; Knowles, Katie; Thompson, Laura; Strachan-Deol, Jack (Physics Special Topics, 2021)
Was the explosion in season 2 of Grey’s Anatomy an accurate representation - if the scenario was to occur in reality? This paper reviews if the outcome and consequences of this explosion have been exaggerated through a mathematical analysis on two subjects affected, and comparing these to observations of the scene. It was found that the effects were greatly exaggerated due to the discrepancies in the energy for vaporisation, 3×10^6kJ, and energy of the explosion experienced by subject 1, 1131kJ. Furthermore, subject 2 would suffer more extensive injuries due to the increase in temperature of 122.5°C experienced on a surface level of the subject’s body.